Talent identification and development issues in modern sport - Čoh Milan (College of Sports and Health, Belgrade, 2019)
Identifying talented young athletes and their timely integration into the process of training the sports discipline best suited to their abilities is one of the most important tasks of sports science and profession. Wrong decisions are numerous and extremely painful. The problem of talented individuals lies in the fact that their abilities are not limited to a single domain, but a number of different ones. The fundamental dilemma is related to the decision concerning the selection of a sports discipline and the time period of engagement in a specific sport. Is early engagement of children in sport beneficial or not? The answer is both yes and no! Early engagement of children in sports is a trend in modern sport. Many young talented athletes burn out too soon. Many coaches and overly ambitious parents often have quite unrealistic expectations from their children's sports results. Talented young athletes often terminate their sports career due to overly ambitious and specific training, injuries and lack of intrinsic motivation.